Kebijakan Formulasi Tindak Pidana Agama dalam KUHP Nasional - Dwinta Yulyanti; Diah Gustiniati Maulani; Maya Shafira; Budi Rizki Husin; Muhammad Farid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Criminal law formulation policy is the initial stage in criminal law politics that establishes legal norms formulated in legislation, including religious offenses. In the National Criminal Code enacted through Law No. 1 Year 2023, this policy is reflected in Article 300 - Article 305 of the National Criminal Code which regulates criminal offenses against religion, belief, and worship. In this case, it is important to analyze how the formulation policy on religious criminal offenses in the National Criminal Code and what are the juridical implications of the formulation policy on religious criminal offenses in the National Criminal Code. The research method used is normative juridical and supported by empirical juridical method. The data used are primary data, secondary data, and tertiary data. The data obtained is then analyzed qualitatively. Based on the results of the research, it is known that in the National Criminal Code passed through Law No. 1 of 2023, In Article 300 to Article 305 of the National Criminal Code, the state attempts to reorganize religious offenses by clarifying the elements of the act and the intention of the perpetrator, thus preventing multiple interpretations and abuse of the law. This formulation also expands the reach of legal protection not only to official religions, but also to public order and diversity of beliefs in society. However, in substance, the juridical implications of the policy formulation of religious criminal articles in the National Criminal Code include higher legal certainty, protection of citizens' constitutional rights, and changes in the orientation of punishment from repressive to more educative and preventive.